Simulation of electromagnetic field distribution in the measuring cell for determining the dielectric permittivity of materials at microwave frequencies - N. A. Pevneva; A. A. Kopshai; A. L. Gurskii (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
To determine the dielectric permittivity of materials in a wide frequency range with the automation of measurements and the necessary accuracy, measuring cells have been created to ensure the simplicity of the design of the waveguide path. In order to obtain information about the suitability of measuring cells based on irregular SHF waveguides for estimation of dielectric parameters of materials, we simulated the structure of electromagnetic field in the system consisting of two irregular waveguides and waveguide chamber placed between them using a three-dimensional electrodynamic simulation in Ansoft HFSS package environment. The distribution of the electric field was simulated when an empty polyethylene tube, a rod of fluoroplastic and a rod of textolite are placed in the measuring cell. It was demonstrated that high order modes fade out in irregular waveguide and do not affect the precision of obtained results, and significant edge effects were not detected. It allows one to utilize measuring cells based on irregular waveguides together with a scalar or vector network analyzer and using the partial filling of the waveguide method or the modified Nicholson – Ross – Weir method for measurements of dielectric permittivity  of materials. The results of modeling the dependence of the amplitude and phase of the reflection coefficient of the textolite and fluoroplastic on the frequency in Ansoft HFSS environment are given. The simulation results are compared with the results obtained experimentally. The frequency dependencies of  were obtained experimentally for test materials – textolite and fluoroplastic – in the frequency range of 25,95–37,50 GHz. The experimental data are in satisfactory agreement with the results of theoretical calculations and do not go beyond the boundaries specified by the measurement uncertainty.